Environmental & Architectural Phenomenology Cumulative Index, Vols. 1–35 (1990–2024) - Kansas State University. Architecture Department (Environmental Architectural Phenomenology, 2025)
This index includes EAP entries except reference items listed in “citations received.” Entries have been identified in the following order: volume number, issue number, and page(s). Thus 3,2:10, for example, refers to volume 3, issue 2, page 10. Volume numbers by years are as follows: vol. 1—1990; vol. 2—1991; vol. 3—1992; vol. 4—1993; vol. 5—1994; vol. 6—1995; vol. 7—1996; vol. 8—1997; vol. 9—1998; vol. 10—1999; vol. 11—2000; vol. 12—2001; vol. 13—2002; vol. 14—2003; vol. 15—2004; vol. 16—2005; vol. 17—2006; vol. 18—2007; vol. 19—2008; vol. 20—2009; vol. 21—2010; vol. 22—2011; vol. 23—2012; vol. 24—2013; vol. 25—2014; vol. 26—2015; vol. 27—2016; vol. 28—2017; vol. 29—2018; vol. 30—2019; vol. 31—2020; vol. 32—2021; vol. 33—2022; vol. 34—2023; vol. 35—2024; vol. 36—2025 [note EAP became digital-copy-only in 2016 and shifted from three to two issues per year].